Electrode modification material and preparation method and application thereof
By using electrode modification materials composed of graphene oxide-doped polyacrylonitrile-based carbon nanofibers and UIO-66-NH2, the problems of expensive lincomycin detection equipment, complex sample pretreatment and low detection sensitivity in the prior art are solved, and efficient and sensitive lincomycin detection are achieved.
Patent Information
- Application Number
- CN202411902541.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The methods used in the detection of lincomycin in the prior art have problems such as expensive equipment, complex sample preprocessing and low detection sensitivity.
An electrode modification material is adopted, which consists of graphene oxide-doped polyacrylonitrile-based carbon nanofibers and UIO-66-NH2. The carbon nanofibers are prepared by electrospinning method and uniformly loaded by solvent method to form electrode modification materials with high conductivity and high electrochemical activity.
The electrocatalytic activity and detection sensitivity of electrode modification materials are improved, and the efficient detection of lincomycin is achieved, with high detection sensitivity, fast detection speed, low equipment cost and reliable detection results.
Smart Images

Figure HDA0005203583430000011 
Figure HDA0005203583430000012 
Figure HDA0005203583430000021
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of chemically modified electrodes, and in particular to an electrode modification material and a preparation method and application thereof. Background Art
[0002] Lincomycin (LIN) is a natural antibacterial drug of the lincosamide class synthesized by Streptomyces, which can treat diseases caused by aerobic or anaerobic Gram-positive bacteria and is widely used in animal husbandry and food production industries. However, excessive use of lincomycin not only leads to bacterial resistance, reduces the effectiveness of the drug or makes it ineffective, but also causes environmental pollution and threatens human health.
[0003] There are many methods for detecting lincomycin, including surface enhanced Raman spectroscopy (SERS), liquid chromatography-tandem mass spectrometry (LC-MS / MS), accelerated solvent-solid phase extraction-gas chromatography-mass spectrometry (ASE / SPE-GC / MS), high performance liquid chromatography, high performance liquid chromatography-mass spectrometry / tandem mass spectrometry (HPLC–MS / MS-TOF), etc. However, these methods generally have defects such as expensive equipment and complex sample pretreatment, which limits their practical application. Electrochemiluminescence (ECL) has the advantages of simple operation, low price and fast analysis speed, and has the potential to be used for rapid detection of lincomycin, but there is a problem of low detection sensitivity. Summary of the invention
[0004] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, one of the purposes of the present invention is to provide an electrode modification material; the second purpose of the present invention is to provide a method for preparing the electrode modification material; the third purpose of the present invention is to provide a chemically modified electrode; the fourth purpose of the present invention is to provide an electrochemiluminescence sensor; the fifth purpose of the present invention is to provide the application of the chemically modified electrode or electrochemiluminescence sensor.
[0005] The basic principle of the present invention is described as follows:
[0006] 1) Metal organic framework materials (MOFs) have the advantages of large specific surface area, high porosity, and surface modification, and are often used as electrode modification materials. However, MOFs usually have the problem of poor stability in aqueous solution. The Zr-based metal organic framework UIO-66-NH2 containing amino functional groups forms a strong coordination bond between the metal node (Zr) and the organic linker (uracil), which can limit the coordinated water molecules of the Zr node, thereby enhancing the stability of the framework and reducing the dissolution of the framework in water. In addition, the amino group can form hydrogen bonds with water molecules, which enhances the dispersibility of the framework in water. Therefore, the present invention selects the metal organic framework UIO-66-NH2 with good stability in aqueous solution as the basis of the electrode modification material;
[0007] 2) UIO-66-NH2 has a low inherent conductivity, so the present invention improves its conductivity and electrochemical activity by combining it with a highly conductive material. Among a variety of highly conductive materials, carbon nanofiber materials (CNFs) have the advantages of good conductivity, corrosion resistance, high temperature resistance, small mass and low cost;
[0008] 3) The performance of carbon nanofiber materials is closely related to the physical and structural properties of their precursor fibers. Polyacrylonitrile (PAN) is a high molecular polymer. The polyacrylonitrile-based carbon nanofibers prepared with polyacrylonitrile as a precursor have the characteristics of high specific surface area and high stability.
[0009] 4) Filling nanoparticles in the precursor fiber can improve the strength, hardness and conductivity of the carbon nanofibers. Graphene oxide (GO) has higher amphiphilicity and reactivity than other nanomaterials, and also has the advantages of large specific surface area, good dispersibility, and multiple functional groups. Therefore, the present invention selects polyacrylonitrile filled with graphene oxide as a precursor to prepare carbon nanofiber material, and combines the carbon nanofiber material with UIO-66-NH2 to obtain an electrode modified material with high conductivity and electrochemical activity.
[0010] In order to achieve the above object, the technical solution adopted by the present invention is:
[0011] A first aspect of the present invention provides an electrode modification material, which includes graphene oxide-doped polyacrylonitrile-based carbon nanofibers and UIO-66-NH2; the UIO-66-NH2 is loaded on the surface of the graphene oxide-doped polyacrylonitrile-based carbon nanofibers.
[0012] In some embodiments of the present invention, the electrode modification material includes the following preparation raw materials: polyacrylonitrile, graphene oxide, a zirconium source, an organic ligand and a solvent.
[0013] In some embodiments of the present invention, the mass ratio of graphene oxide to polyacrylonitrile is 1:(10-15).
[0014] In the present invention, polyacrylonitrile is used as a precursor for preparing carbon nanofibers, and graphene oxide with high amphiphilicity and reactivity, large specific surface area, good dispersibility and many functional groups is used as filling nanoparticles, which can improve the strength, hardness and conductivity of polyacrylonitrile-based carbon nanofibers.
[0015] In some embodiments of the present invention, the zirconium source is selected from at least one of zirconium chloride, zirconium acetate and zirconium sulfate.
[0016] In some specific embodiments of the present invention, the zirconium source is zirconium chloride (ZrCl4).
[0017] In some embodiments of the present invention, the organic ligand is selected from at least one of terephthalic acid, 2-aminoterephthalic acid, 2-methylterephthalic acid, 2-bromoterephthalic acid, 2-nitroterephthalic acid, and 2,4-dichloroterephthalic acid.
[0018] In some specific embodiments of the present invention, the organic ligand is 2-aminoterephthalic acid.
[0019] In some specific embodiments of the present invention, the mass ratio of the zirconium source to the organic ligand is 1:(1-1.3).
[0020] In some embodiments of the present invention, the solvent is selected from at least one of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), and N-methylpyrrolidone (NMP).
[0021] In some specific embodiments of the present invention, the solvent is N,N-dimethylformamide.
[0022] The second aspect of the present invention provides a method for preparing the electrode modifying material according to the first aspect of the present invention, comprising the following steps:
[0023] S1, mixing polyacrylonitrile, graphene oxide and a solvent to form a precursor solution, and electrospinning to obtain graphene oxide-doped polyacrylonitrile fibers;
[0024] S2, carbonizing the graphene oxide-doped polyacrylonitrile fiber to obtain graphene oxide-doped polyacrylonitrile-based carbon nanofibers;
[0025] S3, mixing the zirconium source, the organic ligand and the solvent, adding the graphene oxide-doped polyacrylonitrile-based carbon nanofibers to form a suspension, heating the suspension to react, and obtaining the electrode modification material.
[0026] In some embodiments of the present invention, in step S1, the ratio of graphene oxide, polyacrylonitrile and solvent is 1 g: (10-15) g: (25-35) mL.
[0027] In some specific embodiments of the present invention, in step S1, the ratio of graphene oxide, polyacrylonitrile and solvent is 1 g:(10-12) g:(25-30) mL.
[0028] In some embodiments of the present invention, in step S1, the graphene oxide, polyacrylonitrile and solvent are mixed and stirred at 20-25° C. for 10-15 hours to form a precursor solution.
[0029] In some embodiments of the present invention, in step S1, the electrospinning process parameters include at least one of the following parameters:
[0030] 1) The needle distance is 15-20cm;
[0031] 2) The speed of the wire drum is 160-220r / min;
[0032] 3) Voltage is 11-15kV;
[0033] 4) The injection rate is 1-2 mL / h.
[0034] In some specific embodiments of the present invention, in step S1, the electrospinning process parameters include at least one of the following parameters:
[0035] 1) The needle distance is 15-18cm;
[0036] 2) The speed of the wire drum is 160-180r / min;
[0037] 3) Voltage is 11-13kV;
[0038] 4) The injection rate is 1-1.5 mL / h.
[0039] In the present invention, polyacrylonitrile is used as a precursor to prepare polyacrylonitrile-based carbon nanofibers through an electrostatic spinning method, so that the carbon nanofibers have a high specific surface area and high stability.
[0040] In some embodiments of the present invention, in step S2, the carbonization includes first heating the temperature to 200-250°C at a rate of 5-10°C / min, keeping it warm for 2-3 hours for pre-oxidation, and then heating the temperature to 600-800°C at a rate of 5-10°C / min under a protective atmosphere, and keeping it warm for 3-5 hours.
[0041] In some specific embodiments of the present invention, in step S2, the carbonization includes first heating the temperature to 230-250°C at a rate of 5-7°C / min, keeping it warm for 2-2.5 hours for pre-oxidation, and then heating the temperature to 600-700°C at a rate of 5-7°C / min under a protective atmosphere, and keeping it warm for 3-4 hours.
[0042] In some embodiments of the present invention, in step S2, the protective atmosphere includes nitrogen.
[0043] In the present invention, the graphene oxide-doped polyacrylonitrile fiber is first placed in a muffle furnace for pre-oxidation, and then transferred to a tubular furnace for high-temperature carbonization under a protective atmosphere, which can ensure that the graphene oxide-doped polyacrylonitrile fiber is completely carbonized to obtain graphene oxide-doped polyacrylonitrile-based carbon nanofibers with excellent performance.
[0044] In some embodiments of the present invention, in step S3, the ratio of the zirconium source, the organic ligand and the solvent is 1 g: (1-1.3) g: (60-120) mL.
[0045] In some specific embodiments of the present invention, in step S3, the ratio of the zirconium source, the organic ligand and the solvent is 1 g: (1-1.1) g: (60-100) mL.
[0046] In some embodiments of the present invention, in step S3, the mass ratio of the zirconium source to the graphene oxide-doped polyacrylonitrile-based carbon nanofibers is 1:(0.1-1.5).
[0047] In some specific embodiments of the present invention, in step S3, the mass ratio of the zirconium source to the graphene oxide-doped polyacrylonitrile-based carbon nanofibers is 1:(0.1-1.3).
[0048] In some embodiments of the present invention, in step S3, the zirconium source, organic ligand and solvent are mixed and then stirred at 20-25° C. for 25-35 min.
[0049] In some embodiments of the present invention, in step S3, after adding the graphene oxide-doped polyacrylonitrile-based carbon nanofibers, stirring is carried out at 20-25° C. for 25-35 minutes to obtain a suspension.
[0050] In some embodiments of the present invention, in step S3, the heating reaction temperature is 100-120° C. and the time is 12-18 hours.
[0051] In some specific embodiments of the present invention, in step S3, the heating reaction is carried out at a temperature of 110-120° C. and for a time of 12-15 hours.
[0052] In the present invention, a zirconium source, an organic ligand and a solvent are first mixed and reacted to form UIO-66-NH2, and then UIO-66-NH2 is uniformly loaded on the surface of graphene oxide-doped polyacrylonitrile-based carbon nanofibers through a solvent method to form a uniformly dispersed electrode modification material, thereby avoiding the problem of large-scale agglomeration of UIO-66-NH2 and improving the electrocatalytic activity of the electrode modification material.
[0053] In some embodiments of the present invention, in step S3, after the heating reaction is completed, washing and drying steps are also included.
[0054] In some embodiments of the present invention, the washing reagent includes methanol, N,N-dimethylformamide and ethanol.
[0055] In some embodiments of the present invention, the drying temperature is 50-70°C.
[0056] In some embodiments of the present invention, the drying time is 8-12 hours.
[0057] The third aspect of the present invention provides a chemically modified electrode, the surface of which carries the electrode modification material described in the first aspect of the present invention.
[0058] In some embodiments of the present invention, the chemically modified electrode is prepared by a method comprising the following steps: polishing, washing and drying the electrode to be modified, grinding the electrode modification material and adding a dispersion liquid, ultrasonically dispersing to form a suspension, taking the suspension and dropping it onto the electrode to be modified, and drying to obtain the chemically modified electrode.
[0059] In some embodiments of the present invention, the dispersion is a mixture of ultrapure water, isopropanol and perfluororesin solution (5 wt % Nafion solution) in a volume ratio of (15-17):(3-5):1.
[0060] In some embodiments of the present invention, in the suspension, the concentration of the electrode modification material is (1-1.5) mg / mL.
[0061] In some embodiments of the present invention, the amount of the electrode modification material is 5-10 μg / electrode to be modified.
[0062] In some embodiments of the present invention, the electrode to be modified comprises a glassy carbon electrode (GCE).
[0063] In some embodiments of the present invention, the washing reagent for the electrode to be modified includes water and ethanol.
[0064] The fourth aspect of the present invention provides an electrochemiluminescence sensor, comprising the chemically modified electrode described in the third aspect of the present invention.
[0065] In some embodiments of the present invention, the electrochemiluminescence sensor includes an Ag / AgCl electrode as a reference electrode, a Pt electrode as a counter electrode, and the chemically modified electrode as a working electrode.
[0066] The fifth aspect of the present invention provides the use of the chemically modified electrode described in the third aspect of the present invention, or the electrochemiluminescence sensor described in the fourth aspect in the detection of lincomycin.
[0067] In some embodiments of the invention, the use comprises detecting lincomycin (LIN) in milk.
[0068] Compared with the prior art, the beneficial effects of the present invention include:
[0069] 1) The electrode modification material provided by the present invention is a polyacrylonitrile-based carbon nanofiber doped with graphene oxide having UIO-66-NH2 uniformly dispersed on the surface. UIO-66-NH2 has good stability in water, large specific surface area, and high porosity. Graphene oxide improves the strength, hardness, and conductivity of the carbon nanofiber. After UIO-66-NH2 is combined with the polyacrylonitrile-based carbon nanofiber doped with graphene oxide, the conductivity and electrochemical activity are improved. The obtained electrode modification material has a cross-linked network structure, a large specific surface area, many active sites, and high electrocatalytic activity.
[0070] 2) The preparation method of the electrode modification material provided by the present invention has simple steps, and the polyacrylonitrile-based carbon nanofibers are prepared by electrospinning, which can make the carbon nanofibers have a high specific surface area and high stability. UIO-66-NH2 is loaded on the surface of the carbon nanofibers by a solvent method, which can avoid a large amount of UIO-66-NH2 agglomeration, thereby ensuring the electrocatalytic activity of the electrode modification material;
[0071] 3) The electrochemically modified electrode provided by the present invention, after being modified with an electrode modification material, can be used as a working electrode of an electrochemical luminescence sensor with high detection sensitivity;
[0072] 4) The electrochemiluminescence sensor containing the electrochemically modified electrode provided by the present invention can be applied to the detection of lincomycin, and has high detection sensitivity, fast detection speed, low equipment cost and reliable detection results. BRIEF DESCRIPTION OF THE DRAWINGS
[0073] Figure 1 SEM images of PAN / CNFs, GO, GO / PAN / CNFs and UIO-66-NH2 / GO / PAN / CNFs;
[0074] Figure 2 TEM image of the electrode modified material in Example 1;
[0075] Figure 3 EDS distribution diagram of the electrode modification material C (a), O (b), N (c), and Zr (d) in Example 1;
[0076] Figure 4 XRD diffraction patterns of UIO-66-NH2, GO / PAN / CNFs and UIO-66-NH2 / GO / PAN / CNFs;
[0077] Figure 5 This is the XPS graph of the electrode modified material in Example 1;
[0078] Figure 6 This is the C1s characteristic peak spectrum of the electrode modification material in Example 1;
[0079] Figure 7 This is the N1s characteristic peak spectrum of the electrode modification material in Example 1;
[0080] Figure 8 This is the O1s characteristic peak spectrum of the electrode modification material in Example 1;
[0081] Fig. 9 This is the Zr3d characteristic peak spectrum of the electrode modification material in Example 1;
[0082] Fig.10 For Ru(bpy)3 in Application Example 5 2+ -CV curves of LIN system on different working electrodes;
[0083] Fig.11 For Ru(bpy)3 in Application Example 5 2+ -LIN system ECL curves on different working electrodes. DETAILED DESCRIPTION
[0084] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.
[0085] The molecular weight of polyacrylonitrile used in the following examples and comparative examples is Mw=150000 g / mol; N,N-dimethylformamide is analytical grade and purchased from Guangdong Guanghua Technology Co., Ltd.; graphene oxide is purchased from Shenzhen Suiheng Technology Co., Ltd.; Nafion solution (5wt%) is purchased from Shanghai Hesen Electric Co., Ltd.; the concentration of phosphate buffer (PBS) is 0.1 mol / L, with Na2HPO4 and NaH2PO4 as raw materials, and H3PO4 and KOH to adjust the pH.
[0086] Example 1
[0087] This embodiment prepares an electrode modification material, and the steps are as follows:
[0088] S11, adding 1g of graphene oxide and 10g of polyacrylonitrile to 27mL of N,N-dimethylformamide, stirring at room temperature for 12h to obtain an electrospinning precursor solution; transferring the precursor solution to a syringe, the distance between the rollers at the tip of the syringe (needle distance) is 16.6cm, the speed of the roller with aluminum foil (receiving drum speed) is 160r / min, and electrospinning is performed at an injection speed of 1.5mL / h under a high voltage of 11.03kV to obtain graphene oxide-doped polyacrylonitrile fibers;
[0089] S12, placing the graphene oxide doped polyacrylonitrile fiber in a muffle furnace, heating it to 250°C at a rate of 5°C / min, and keeping it warm for 2 hours for pre-oxidation, then transferring the material to a tube furnace, heating it to 600°C at a rate of 5°C / min under a N2 atmosphere, and keeping it warm at this temperature for 3 hours to ensure that the material is carbonized, and cooling it to room temperature to obtain graphene oxide doped polyacrylonitrile-based carbon nanofibers;
[0090] S13, 0.83g ZrCl4 and 0.89g 2-aminoterephthalic acid were dissolved in 50mL N,N-dimethylformamide, stirred at room temperature for 30min to mix evenly, then 0.5g graphene oxide-doped polyacrylonitrile-based carbon nanofibers were added, and stirring was continued for 30min to obtain a uniformly dispersed suspension, and the suspension was transferred to a Teflon-lined autoclave and heated to 120°C for reaction for 12h, and then the product was collected at room temperature, washed thoroughly with methanol, N,N-dimethylformamide and ethanol, and dried under vacuum at 60°C overnight to obtain an electrode modified material (UIO-66-NH2 / GO / PAN / CNFs).
[0091] Comparative Example 1
[0092] This comparative example prepares a polyacrylonitrile-based carbon nanofiber in the following steps:
[0093] 1) 10 g of polyacrylonitrile was added to 27 mL of N,N-dimethylformamide and stirred at room temperature for 12 h to obtain an electrospinning precursor solution; the precursor solution was transferred to a syringe, the distance between the tip roller of the syringe (needle distance) was 16.6 cm, the speed of the roller with aluminum foil (receiving drum speed) was 160 r / min, and electrospinning was performed at an injection speed of 1.5 mL / h under a high voltage of 11.03 kV to obtain polyacrylonitrile fiber;
[0094] 2) Place the polyacrylonitrile fiber in a muffle furnace, heat it to 250°C at a rate of 5°C / min, and keep it for 2 h for pre-oxidation. Then transfer the material to a tubular furnace, heat it to 600°C at a rate of 5°C / min under a N2 atmosphere, and keep it at this temperature for 3 h to ensure that the carbonization of the material is complete. Cool it to room temperature to obtain polyacrylonitrile-based carbon nanofibers (PAN / CNFs).
[0095] Comparative Example 2
[0096] This comparative example prepares a graphene oxide-doped polyacrylonitrile-based carbon nanofiber, and the steps are as follows:
[0097] 1) 1 g of graphene oxide and 10 g of polyacrylonitrile were added to 27 mL of N,N-dimethylformamide and stirred at room temperature for 12 h to obtain an electrospinning precursor solution; the precursor solution was transferred to a syringe, the distance between the rollers at the tip of the syringe (needle distance) was 16.6 cm, the speed of the roller with aluminum foil (winding drum speed) was 160 r / min, and electrospinning was performed at an injection speed of 1.5 mL / h under a high voltage of 11.03 kV to obtain graphene oxide-doped polyacrylonitrile fibers;
[0098] 2) The graphene oxide-doped polyacrylonitrile fibers were placed in a muffle furnace, heated to 250 °C at a rate of 5 °C / min, and kept warm for 2 h for pre-oxidation. The material was then transferred to a tubular furnace, heated to 600 °C at a rate of 5 °C / min under a N2 atmosphere, and kept warm at this temperature for 3 h to ensure that the carbonization of the material was complete. The material was cooled to room temperature to obtain graphene oxide-doped polyacrylonitrile-based carbon nanofibers (GO / PAN / CNFs).
[0099] Comparative Example 3
[0100] This comparative example prepares a UIO-66-NH2, and the steps are as follows:
[0101] 1) Dissolve 0.83 g ZrCl4 and 0.89 g 2-aminoterephthalic acid in 50 mL N,N-dimethylformamide, and stir at room temperature for 30 min to mix them evenly to obtain a homogeneous solution;
[0102] 2) The homogeneous solution was placed in a Teflon-lined autoclave and heated at 120°C for 12 hours. After the reaction was completed, it was naturally cooled to room temperature. The powder was collected by filtration, washed thoroughly with methanol, N,N-dimethylformamide and ethanol, and dried under vacuum at 60°C overnight to obtain UIO-66-NH2.
[0103] Application Example 1
[0104] This application example provides a chemically modified electrode, the steps are as follows:
[0105] 1) Polish the glassy carbon electrode on suede with 0.5 μm alumina powder, clean the electrode with ultrapure water and ethanol, and blow dry with N2 for later use;
[0106] 2) Grind the electrode modification material UIO-66-NH2 / GO / PAN / CNFs prepared in Example 1 into powder, take 1 mg of the powder and add it into 1 mL of dispersion solution (ultrapure water: isopropanol: Nafion solution = 16:4:1, v / v / v), and ultrasonically disperse for 30 min to obtain a UIO-66-NH2 / GO / PAN / CNFs suspension;
[0107] 3) Use a pipette to transfer 5 μL of UIO-66-NH2 / GO / PAN / CNFs suspension to modify the glassy carbon electrode, place it at room temperature to dry, and obtain a chemically modified electrode (UIO-66-NH2 / GO / PAN / CNFs / GCE).
[0108] Application Example 2
[0109] This application example provides a chemically modified electrode, the steps are as follows:
[0110] 1) Polish the glassy carbon electrode on suede with 0.5 μm alumina powder, clean the electrode with ultrapure water and ethanol, and blow dry with N2 for later use;
[0111] 2) Grind the polyacrylonitrile-based carbon nanofibers PAN / CNFs prepared in Comparative Example 1 into powder, take 1 mg of the powder and add it into 1 mL of dispersion solution (ultrapure water: isopropanol: Nafion solution = 16:4:1, v / v / v), and ultrasonically disperse for 30 min to obtain a PAN / CNFs suspension;
[0112] 3) Use a pipette to transfer 5 μL of PAN / CNFs suspension to modify the glassy carbon electrode, and place it at room temperature to dry to obtain a chemically modified electrode (PAN / CNFs / GCE).
[0113] Application Example 3
[0114] This application example provides a chemically modified electrode, the steps are as follows:
[0115] 1) Polish the glassy carbon electrode on suede with 0.5 μm alumina powder, clean the electrode with ultrapure water and ethanol, and blow dry with N2 for later use;
[0116] 2) The graphene oxide-doped polyacrylonitrile-based carbon nanofibers GO / PAN / CNFs prepared in Comparative Example 2 were ground into powder, 1 mg of the powder was added into 1 mL of a dispersion solution (ultrapure water: isopropanol: Nafion solution = 16:4:1, v / v / v), and ultrasonically dispersed for 30 min to obtain a GO / PAN / CNFs suspension;
[0117] 3) Use a pipette to transfer 5 μL of GO / PAN / CNFs suspension to modify the glassy carbon electrode, and place it at room temperature to dry to obtain a chemically modified electrode (GO / PAN / CNFs / GCE).
[0118] Application Example 4
[0119] This application example provides a chemically modified electrode, the steps are as follows:
[0120] 1) Polish the glassy carbon electrode on suede with 0.5 μm alumina powder, clean the electrode with ultrapure water and ethanol, and blow dry with N2 for later use;
[0121] 2) Grind the UIO-66-NH2 prepared in Comparative Example 3 into powder, take 1 mg of the powder and add it into 1 mL of dispersion solution (ultrapure water: isopropanol: Nafion solution = 16:4:1, v / v / v), and ultrasonically disperse for 30 min to obtain a UIO-66-NH2 suspension;
[0122] 3) Use a pipette to transfer 5 μL of UIO-66-NH2 suspension to modify the glassy carbon electrode, and place it at room temperature to dry to obtain a chemically modified electrode (UIO-66-NH2 / GCE).
[0123] Application Example 5
[0124] This application example uses an MPI-E electrochemiluminescence analyzer (Xi'an Ruimai Analytical Instrument Co., Ltd.) to detect lincomycin in milk, using a Pt electrode as the counter electrode, Ag / AgCl as the reference electrode, and the chemically modified electrodes prepared in Application Examples 1-4 as the working electrodes:
[0125] Three different brands of milk were purchased from a supermarket. 1.5 mL of each of the three brands of milk was centrifuged in a centrifuge at 4°C and 10,000 rpm. The supernatant was collected and filtered through a sterile microporous membrane (0.22 μm). 1 mL of the milk sample was added to 10 mL of PBS buffer (pH 7.0) for later use.
[0126] Dissolve tri(2,2-bipyridyl)ruthenium(II) chloride hexahydrate in water and prepare 1×10 -4 mol / LRu(bpy)3 2+ Then take 100μm 1×10 -4 mol / LRu(bpy)3 2+ solution, 100 μ m 0.1 mol / L phosphate buffer, constitutes the electrolyte solution;
[0127] The parameters of the MPI-E electrochemiluminescence analyzer were set as follows: cyclic voltammetry potential range 0.2-1.25 V, scan rate 0.1 V / s, scan segment 2, sampling interval 0.001 V, standing time 4 s, MPI-E instrument detection time 18 s, sampling rate 10 T / s. Under the above parameters, different working electrodes were placed in the electrolyte solution for lincomycin electrochemiluminescence detection, and cyclic voltammetry was used for scanning to record the ECL signal.
[0128] Material Characterization and Performance Testing
[0129] 1. The graphene oxide GO, the polyacrylonitrile-based carbon nanofibers PAN / CNFs in Comparative Example 1, the graphene oxide-doped polyacrylonitrile-based carbon nanofibers GO / PAN / CNFs in Comparative Example 2, and the electrode modification material UIO-66-NH2 / GO / PAN / CNFs in Example 1 were characterized using a SU8220 ultra-high resolution cold field emission scanning electron microscope (SEM, JEOL Ltd.):
[0130] Figure 1 SEM images of PAN / CNFs, GO, GO / PAN / CNFs and UIO-66-NH2 / GO / PAN / CNFs, among which, Figure 1 (a) is the SEM image of polyacrylonitrile-based carbon nanofibers PAN / CNFs in Comparative Example 1, Figure 1 (b) is the SEM image of graphene oxide GO. Figure 1 (c) is the SEM image of graphene oxide-doped polyacrylonitrile-based carbon nanofibers GO / PAN / CNFs in Comparative Example 2, Figure 1 (d) and Figure 1 (e) is the SEM image of the electrode modification material UIO-66-NH2 / GO / PAN / CNFs in Example 1. Figure 1 (a) It can be seen that polyacrylonitrile-based carbon nanofibers are continuous and uniform two-dimensional fibrous structures; Figure 1 (b) It can be seen that graphene oxide has a lamellar structure and is accompanied by surface wrinkles. Figure 1 (c) It can be seen that after adding graphene oxide, the structure of polyacrylonitrile-based carbon nanofibers is affected, and the fibers are transformed from a planar network structure to an obvious staggered three-dimensional network structure. These mutually cross-linked network structures can increase active sites, improve the tension and stability of cross-linked carbon nanofibers, and thus enhance the performance of the material; Figure 1 (d) and Figure 1 (e) It can be seen that the electrode modification material in Example 1 has an interlaced three-dimensional network structure of polyacrylonitrile-based carbon nanofibers.
[0131] 2. The electrode modification material UIO-66-NH2 / GO / PAN / CNFs in Example 1 was characterized by transmission electron microscopy (TEM):
[0132] Figure 2 is the TEM image of the electrode modification material in Example 1, Figure 2 It can be seen that UIO-66-NH2 is uniformly loaded on the surface of polyacrylonitrile-based carbon nanofibers.
[0133] Figure 3 is the EDS distribution diagram of the electrode modification material C (a), O (b), N (c), and Zr (d) in Example 1. Figure 3It can be seen from the analysis of the Mapping results that the electrode modification material in Example 1 is mainly composed of C, N, O and Zr elements, and several elements are evenly distributed in the fibers, indicating that UIO-66-NH2 is evenly distributed on the polyacrylonitrile-based carbon nanofibers.
[0134] 3. The electrode modification material UIO-66-NH2 / GO / PAN / CNFs in Example 1, the graphene oxide-doped polyacrylonitrile-based carbon nanofibers GO / PAN / CNFs in Comparative Example 2, and UIO-66-NH2 in Comparative Example 3 were characterized using a D8 ADVANCE Bruker X-ray diffractometer (XRD, Bruker, Germany):
[0135] Figure 4 XRD diffraction patterns of UIO-66-NH2, GO / PAN / CNFs and UIO-66-NH2 / GO / PAN / CNFs are shown in Figure 2. Figure 4 It can be seen that UIO-66-NH2 exhibits diffraction peaks at 7.3° and 8.5°, which are attributed to the (110) and (200) crystal planes of UIO-66-NH2, indicating that UIO-66-NH2 nanoparticles with high crystallinity are successfully synthesized. The XRD diffraction pattern of UIO-66-NH2 / GO / PAN / CNFs is highly similar to that of UIO-66-NH2, indicating that UIO-66-NH2 is successfully loaded on GO / PAN / CNFs via solvothermal reaction.
[0136] 4. The electrode modified material UIO-66-NH2 / GO / PAN / CNFs in Example 1 was characterized using an ESCALAB 250Xi X-ray photoelectron spectrometer (XPS, Thermo Fisher Scientific, USA):
[0137] Figure 5 This is the XPS graph of the electrode modification material in Example 1, Figure 6 is the C1s characteristic peak spectrum of the electrode modification material in Example 1, Figure 7 This is the N1s characteristic peak spectrum of the electrode modification material in Example 1. Figure 8 This is the O1s characteristic peak spectrum of the electrode modification material in Example 1. Fig. 9 This is the Zr3d characteristic peak spectrum of the electrode modification material in Example 1. Figure 5-Figure 9It can be seen that C in UIO-66-NH2 / GO / PAN / CNFs mainly exists in four forms: C=C (284.70 eV), CO (286.06 eV), CN (287.12 eV) and OCO / C=O (288.80 eV); N in UIO-66-NH2 / GO / PAN / CNFs mainly exists in pyridinic N (399.4 eV), pyrrolic N (400.5 eV), graphitic N (411.3 eV), and quaternary N (43.3 eV). In UIO-66-NH2 / GO / PAN / CNFs, there are five forms of O, namely, N (401.7 eV), C≡N (397.8 eV) and -NH2 (399.06 eV). In UIO-66-NH2 / GO / PAN / CNFs, there are three forms of O, namely, Zr-O (530.20 eV), CO (530.6 eV) and C=O (532.5 eV). In UIO-66-NH2 / GO / PAN / CNFs, there are three forms of Zr, namely, Zr 3d 5 / 2 (182.96 eV) and Zr 3d 3 / 2 (185.40eV) exists in 2 forms.
[0138] Fig.10 For Ru(bpy)3 in Application Example 5 2+ CV curves of the -LIN system on different working electrodes are shown in Figure 2. Fig.10 It can be seen that compared with other modified electrodes, Ru(bpy)3 2+ The oxidation current of -LIN system on UIO-66-NH2 / GO / PAN / GCE increased significantly, but its position hardly changed.
[0139] Fig.11 For Ru(bpy)3 in Application Example 5 2+ -LIN system ECL curves on different working electrodes Fig.11 It can be seen that Ru(bpy)3 2+ The ECL luminescence intensity of the -LIN system on UIO-66-NH2 / GO / PAN / CNFs / GCE is significantly increased, which is about 15 times that of the GCE bare electrode, indicating that UIO-66-NH2 / GO / PAN / CNFs / GCE is effective for Ru(bpy)3 2+ -LIN system has a significant sensitization effect. During the enhancement process, Ru(bpy)3 2+ Oxidized to Ru(bpy)3 3+ The N in the tertiary amine of lincomycin is oxidized to an N cationic radical. Since the radical is extremely unstable, it will immediately dehydrogenate to generate a strongly reducing intermediate LIN*, which will convert Ru(bpy)3 3+ Reduction to excited state Ru(bpy)3 2+ *, when the excited state Ru(bpy)32+ *Return to the ground state Ru(bpy)3 2+ When the luminescence phenomenon occurs, the larger specific surface area of UIO-66-NH2 / GO / PAN / CNFs / CNFs can provide more active sites for the reaction, which helps lincomycin diffuse on the electrode surface and accelerates the electron transfer rate.
[0140] The present invention uses an electrochemiluminescence sensor containing a chemically modified working electrode to detect lincomycin in milk. Table 1 compares the detection limit and linear range of this method with other existing lincomycin detection methods. It can be seen from Table 1 that the detection limit of the lincomycin electrochemiluminescence detection method provided by the present invention is 5.61×10 -10 mol / L, linear range is 1.0×10 -8 -1×10 -4 mol / L, compared with existing detection methods such as mass spectrometry (LC-MS / MS) and common electrochemiluminescence (ECL), it has a lower detection limit and a wider linear range.
[0141] Table 1 Comparison of detection limits and linear ranges of lincomycin detection methods
[0142] method Linear range (mol / L) Detection limit (mol / L) Liquid chromatography (LC) <![CDATA[6.50×10 -6 -3.25×10 -4 ]]> <![CDATA[5.2×10 -8 ]]> Liquid chromatography-tandem mass spectrometry (LC-MS / MS) <![CDATA[1.08×10 -8 -2.17×10 -7 ]]> <![CDATA[4.3×10 -10 ]]> Capillary zone electrophoresis with amperometric detection (CZE–AD) <![CDATA[2.17×10 -6 -3.25×10 -4 ]]> <![CDATA[2.17×10 -6 ]]> Electrochemiluminescence (ECL) <![CDATA[5.0×10 -6 -1.0×10 -4 ]]> <![CDATA[3.10×10 -6 ]]> High performance liquid chromatography-ultraviolet (HPLC-UV) <![CDATA[1.74×10 -7 -4.34×10 -6 ]]> <![CDATA[4.33×10 -8 ]]> Linear Sweep Voltammetry (LSV) <![CDATA[4.5×10 -7 -1.5×10 -4 ]]> <![CDATA[2.0×10 -7 ]]> The present invention <![CDATA[1.0×10 -8 -1.0×10 -4 ]]> <![CDATA[5.61×10 -10 ]]>
[0143] In addition, in order to verify the reliability of the detection results of the electrochemiluminescence sensor containing a chemically modified working electrode, the chemically modified electrode UIO-66-NH2 / GO / PAN / CNFs / GCE prepared in Application Example 1 was used to repeatedly detect lincomycin in milk for 8 times. The ECL signal intensities were 1096.35 au, 1150.51 au, 1177.6 au, 1151.54 au, 1146.48 au, 1167.57 au, 1218.73 au and 1139.51 au, respectively. The relative standard deviation (RSD) of the 8 tests was about 3.16%, indicating that the chemically modified working electrode had a good detection performance. The modified electrode UIO-66-NH2 / GO / PAN / CNFs / GCE has good reproducibility; 8 chemically modified electrodes were prepared again according to the method in Application Example 1, and were used for the detection of lincomycin in milk, respectively. The ECL signal intensities were 1144.52au, 1183.64au, 1117.48au, 1101.39au, 1141.52au, 1122.44au, 1172.6au and 1210.72au, respectively. The RSD value of the ECL intensity obtained by 8 tests was about 3.38%, indicating that the chemically modified electrode prepared by the present invention has good reproducibility. The recovery rate of lincomycin in milk is 93.72%-104.70% (RSD < 5%), and the detection result is highly accurate, indicating that the chemically modified electrode provided by the present invention and the electrochemiluminescence sensor using the chemically modified electrode as the working electrode are suitable for the detection of lincomycin in milk, and have the advantages of fast detection, high detection sensitivity, low cost, simple sample processing and reliable detection results.
Claims
1. An electrode modification material, characterized in that: The electrode modification material comprises graphene oxide doped polyacrylonitrile-based carbon nanofibers and UIO-66-NH2; the UIO-66-NH2 is loaded on the surface of the graphene oxide doped polyacrylonitrile-based carbon nanofibers.
2. The electrode modifying material according to claim 1, characterized in that The electrode modification material comprises the following preparation raw materials: polyacrylonitrile, graphene oxide, a zirconium source, an organic ligand and a solvent.
3. The electrode modifying material according to claim 2, characterized in that The zirconium source is selected from at least one of zirconium chloride, zirconium acetate and zirconium sulfate; And / or, the organic ligand is selected from at least one of terephthalic acid, 2-aminoterephthalic acid, 2-methylterephthalic acid, 2-bromoterephthalic acid, 2-nitroterephthalic acid, and 2,4-dichloroterephthalic acid; And / or, the solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone.
4. The method for preparing the electrode modifying material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, mixing polyacrylonitrile, graphene oxide and a solvent to form a precursor solution, and electrospinning to obtain graphene oxide-doped polyacrylonitrile fibers; S2, carbonizing the graphene oxide-doped polyacrylonitrile fiber to obtain graphene oxide-doped polyacrylonitrile-based carbon nanofibers; S3, mixing the zirconium source, the organic ligand and the solvent, adding the graphene oxide-doped polyacrylonitrile-based carbon nanofibers to form a suspension, heating the suspension to react, and obtaining the electrode modification material.
5. The preparation method according to claim 4, characterized in that: In the step S1, the ratio of graphene oxide, polyacrylonitrile and solvent is 1 g: (10-15) g: (25-35) mL; And / or, the electrospinning process parameters include at least one of the following parameters: 1) The needle distance is 15-20cm; 2) The speed of the wire drum is 160-220r / min; 3) Voltage is 11-15kV; 4) The injection rate is 1-2 mL / h.
6. The preparation method according to claim 4, characterized in that: In the step S2, the carbonization includes first heating to 200-250°C at a rate of 5-10°C / min, keeping warm for 2-3h for pre-oxidation, and then heating to 600-800°C at a rate of 5-10°C / min under a protective atmosphere, and keeping warm for 3-5h.
7. The preparation method according to claim 4, characterized in that: In the step S3, the ratio of the zirconium source, the organic ligand and the solvent is 1 g: (1-1.3) g: (60-120) mL; and / or, the mass ratio of the zirconium source to the graphene oxide-doped polyacrylonitrile-based carbon nanofibers is 1:(0.1-1.5); And / or, the heating reaction is carried out at a temperature of 100-120° C. and for a time of 12-18 hours.
8. A chemically modified electrode, characterized in that The surface of the chemically modified electrode carries the electrode modification material according to any one of claims 1 to 3.
9. An electrochemiluminescence sensor, characterized in that: Comprising the chemically modified electrode as described in claim 8.
10. Use of the chemically modified electrode according to claim 8 or the electrochemiluminescence sensor according to claim 9 in the detection of lincomycin.
Citation Information
Patent Citations
CoMn-ZIF@CNF nano composite material and preparation method thereof and aptamer sensor
CN111218118A
Electrode material for wearable health monitoring sensor and preparation method and application thereof
CN117030816A
Voice interaction at a primary device to access call functionality of a companion device
KR102136962B1
Cited By
Method for folding graphene oxide
CN120157116A